The analgesic effect of different interactive modes of virtual reality: A prospective functional near-infrared spectroscopy (fNIRS) study - Deng, Xue; Jian, Chuyao; Yang, Qinglu; Jiang, Naifu; Huang, Zhaoyin; Zhao, Shaofeng (Frontiers in Neuroscience, 2022)
Virtual reality has demonstrated its analgesic effectiveness. However, its optimal interactive mode for pain relief is yet unclear, with rare objective measurements that were performed to explore its neural mechanism. Objective This study primarily aimed at investigating the analgesic effect of different VR interactive modes via functional near-infrared spectroscopy (fNIRS) and exploring its correlations with the subjectively reported VR experience through a self-rating questionnaire. Methods Fifteen healthy volunteers (Age: 21.93 ± 0.59 years, 11 female, 4 male) were enrolled in this prospective study. Three rounds of interactive mode, including active mode, motor imagery (MI) mode, and passive mode, were successively facilitated under consistent noxious electrical stimuli (electrical intensity: 23.67 ± 5.69 mA). Repeated-measures of analysis of variance (ANOVA) was performed to examine its pain relief status and cortical activation, with post hoc analysis after Bonferroni correction performed. Spearman's correlation test was conducted to explore the relationship between VR questionnaire (VRQ) items and cortical activation. Results A larger analgesic effect on the active (−1.4(95%CI, −2.23 to −0.57), p = 0.001) and MI modes (−0.667(95%CI, −1.165 to −0.168), p = 0.012) was observed compared to the passive mode in the self–rating pain score, with no significant difference reported between the two modes (−0.733(95%CI, −1.631 to.165), p = 0.131), associated with diverse activated cortical region of interest (ROI) in charge of motor and cognitive functions, including the left primary motor cortex (LM1), left dorsal–lateral prefrontal cortex (LDLPFC), left primary somatosensory cortex (LS1), left visual cortex at occipital lobe (LOL), and left premotor cortex (LPMC). On the other hand, significant correlations were found between VRQ items and different cortical ROIs (r = −0.629 to 0.722, p < 0.05) as well as its corresponding channels (r = −0.599 to 0.788, p < 0.05). Conclusion Our findings suggest that VR can be considered as an effective non-invasive approach for pain relief by modulating cortical pain processing. A better analgesic effect can be obtained by exciting and integrating cortical ROIs in charge of motor and cognitive functions. The interactive mode can be easily tailored to be in line with the client's characteristics, in spite of the diverse cortical activation status when an equivalent analgesic effect can be obtained.